Peningkatan Brand Awareness Pada Marketing Kepada UMKM Di Desa Karangan Kabupaten Jombang - Danang Radistya; Zawawi Zawawi (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The lack of branding awareness knowledge of MSMEs Desa Karang is a problem for most MSMEs in marketing. Therefore, assistance regarding brand awareness knowledge needs to be given to MSMEs in Karangan Village. Knowledge aboudt the importance of brand awareness and what can boost brand awareness in MSMEs in Karangan Village is certainly an important thing that needs to be done. The main objective of this activity is to provide knowledge regarding the importance of brand awareness for MSMEs in terms of marketing. This activity was carried out using survey and observation methods, interviews, discussions and implementation. The results achieved from this activity are that MSME actors in Karangan village understand the importance of brand awareness for their MSMEs and apply it to the MSMEs they run.